Research Databases in Serbia & Information Dissemination - Brooks, Sam (Infotheca - Journal for Digital Humanities; Vol 10 No 1/2 (2009): Infotheca - Journal of Informatics and Librarianship, 2024)
Through a detailed review of STM and business content available in Serbia, this article depicts the value of particular databases and the impact of a tremendous influx of information into the country in recent years. The two most comprehensive databases are provided by EBSCO Publishing (EBSCO), the world’s largest intermediary between publishers and libraries. EBSCO’s company approach with regard to its academic databases is described. The article also examines which databases are strongest in each discipline, and covers issues such as the availability of journals mostcited, full-text formats, peer-review status, embargo periods, backfiles, and other important issues. Dissemination of, and access to, information is heightened through linking technology inherent in these research databases. The availability and customization of these links is explored. The ability of users to easily review relevant images directly from the results page is also discussed